Global earnings inequality, 1970-2015 - Olle Hammar; Daniel Waldenström (Uppsala University, Department of Economics, 2017)
We estimate trends in global earnings dispersion across occupational groups using a new database covering 66 developed and developing countries between 1970 and 2015. Our main finding is that global earnings inequality has declined, primarily during the 2000s, when the global Gini coefficient dropped nearly 10 points and the earnings share of the world's poorest half doubled. Decomposition analyses emphasize the role of income convergence between poor and rich countries and that earnings have become more similar within occupations in traded industries. Sensitivity checks show that the results are robust to varying real exchange rates, inequality measures and population definitions.
urn:nbn:se:uu:diva-321879
Keywords: D31; F01; O15; 330; Global inequality; Development; Inequality decomposition; Labor markets; Einkommensverteilung; Wirtschaftliche Konvergenz; Gini-Koeffizient; Schätzung; Welt; Industrieländer; Entwicklungsländer